THE EPIDEMIOLOGICAL SITUATION OF MENINGOCOCCAL INFECTION (World Bulletin of Public Health, 2024)
The global decline in the incidence rate of meningococcal infection, which is observed in the last decade, does not exclude the possibility of new outbreaks, epidemics and pandemics. The previous pandemic of meningococcal infection in the world was noted in the 70s. last century, when the incidence rate reached 16-17 people per 100 thousand people. Epidemics of meningococcal infection occur unexpectedly and still cannot be predicted. Currently, MI cases are recorded in more than 150 countries of the world, and Uzbekistan is one of them. The article presents long-term observations (analysis of the age structure of the incidence of meningococcal infection, a monthly analysis of the incidence in the city of Tashkent) and some epidemiological features of meningococcal infection in the world and in Uzbekistan